Analisis Sistem Informasi Akuntansi Pembiayaan Murabahah Berdasarkan PSAK No. 102 di PT. BPR Syariam Dinar Ashri Kantor Cabang Aikmel Desa Bagik Nyaka Kecamatan Aikmel Kabupaten Lombok Timur. - Su'ud Wahedi; Hanizar Hanizar (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2024)
An accounting information system is a collection of resources, such as people and equipment that are arranged to organize data into information. This information is communicated to various decision makers. Accounting information systems realize these changes whether manually or computerized. With the existence of an accounting information system, financing activities within a company can be carried out as well as possible. Apart from that, having a good accounting information system will also be able to provide useful information for management, so that management can make the right decisions in carrying out financing activities that can increase financing and monitor the company's development. Therefore, with the development of Sharia financial institutions, BPRS feel the need to change BPRS services for the better. The role of technology is very helpful in changing services from manual to computerized. Not only that, the role of technology is also to produce data and information whose truth can be verified.This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The data analysis techniques in this research are through data reduction, data presentation and data verification.The research results obtained from this research are the application of the murabahah financing accounting information system at BPR Syariah Dinar Ashri Aikmel Office, namely using computers. Collect customer transaction data, then input the data into an existing system to obtain information. And the implementation of the murabahah financing accounting information system is in accordance with PSAK No. 102 at BPR Syariah Dinar Ashri Aikmel Branch Office.